Canakinumab as treatment for COVID-19-related pneumonia: A prospective case-control study. (March 2021) - Generali, Daniele; Bosio, Giancarlo; Malberti, Fabio; Cuzzoli, Antonio; Testa, Sophie; Romanini, Laura; Fioravanti, Antonio; Morandini, Alessandro; Pianta, Luca; Giannotti, Guglielmo; Viola, Erika Maria; Giorgi-Pierfranceschi, Matteo; et al.
Highlights: Canakinumab is an IL-1β antibody that neutralises the activity of IL-1β. The effects of canakinumab in patients with COVID-19-related pneumonia were studied. 33 patients received canakinumab and 15 received institutional standard of care. Treatment with canakinumab rapidly restored normal oxygen status. Canakinumab was also associated with favorable prognosis versus standard of care. Abstract: Objectives: Canakinumab is an IL-1β antibody that neutralises the activity of IL-1β. This study examined the efficacy and safety of canakinumab in patients with moderate COVID-19-related pneumonia. Design: This study aimed to evaluate the reduction in duration of hospitalisation with adequate oxygen status. Forty-eight patients with moderate COVID-19-related pneumonia were asked to participate in the prospective case-control study: 33 patients (cases) signed informed consent and received canakinumab (Cohort 1) and 15 patients (Controls) refused to receive the experimental drug and received institutional standard of care (Cohort 2). Results: Hospital discharge within 21 days was seen in 63% of patients in Cohort 1 vs. 0% in Cohort 2 (median 14 vs. 26 days, respectively; p < 0.001). There was significant clinical improvement in ventilation regimes following administration of canakinumab compared with Cohort 2 (Stuart-Maxwell test for paired data, p < 0.001). Patients treated with canakinumab experienced a significant increase in PaO2 :FiO2 ( p < 0.001) and reduction in lung damage by CT ( p = 0.01), along with significant decreases in immune/inflammation markers that were not observed in Cohort 2. Only mild side-effects were seen in patients treated with canakinumab; survival at 60 days was 90.0% (95% CI 71.9–96.7) in patients treated with canakinumab and 73.3% (95% CI 43.6–89.1) for Cohort 2. Conclusions: Treatment with canakinumab in patients with COVID-19-related pneumonia rapidly restored normal oxygen status, decreased the need for invasive mechanical ventilation, and was associated with earlier hospital discharge and favourable prognosis versus standard of care.